S-RNase gene of Nicotiana alata is expressed in developing pollen. - Dodds, P N (1993)
In the solanaceous plant Nicotiana alata, self-incompatibility is controlled by a single, multiallelic locus (S locus) expressed in both pollen and pistil. Previously, we have shown cosegregation between alleles of the S locus and alleles of a gene that encodes a glycoprotein with ribonuclease activity (S-RNase). Furthermore, expression of the S-RNase gene is apparently confined to the pistil and is correlated with the onset of self-incompatibility. In this paper, we report that the S-RNase gene is also expressed at low levels in developing pollen. A transcript in developing pollen hybridized to a cDNA encoding the S2-RNase allele of the parent plant and did not hybridize to cDNAs encoding other S-RNase alleles. Two cDNAs for the S2-RNase were cloned from a library derived from anthers of a plant homozygous for the S2 allele and both corresponded to the coding sequence of the S2-RNase. The product of the S-RNase gene was detected by immunocytochemistry in the intine of mature, hydrated pollen grains. These results are interpreted in the light of current knowledge of the structure of the S locus.